ATIVIDADE FÍSICA, OBESIDADE ABDOMINAL E COMPRA DE MEDICAMENTOS EM ADULTOS: ESTUDO TRANSVERSAL RETROSPECTIVO COM USUÁRIOS DA ATENÇÃO BÁSICA DE SAÚDE - Turi, Bruna Camilo; Codogno, Jamile Sanches; Fernandes, Rômulo Araújo; Monteiro, Henrique Luiz (Universidade Estadual de Maringá, 2015)
The aim of the study was to determine associations between physical activity, abdominal obesity and purchase of medicines by users of the Brazilian public healthcare system of the city of Bauru/SP. The sample was composed of adults aged 50 years and through face-to-face interview were collected information about drug utilization, physical activity, economic status and smoking habits. Body mass index and abdominal perimeter composed markers of general and abdominal obesity. The main results found that the purchase of drugs was higher among women, people over 65, non-smokers and those with abdominal obesity. Inversely, active individuals bought fewer medicines when compared to physically inactive. Finally, when physical inactivity and abdominal obesity were aggregated into a single variable, only people physically inactive and physically inactive with abdominal obesity had increased chances of buying drugs in the last month.

O objetivo do estudo foi verificar associações entre prática de atividades físicas, obesidade abdominal e compra de medicamentos por usuários do sistema público de saúde da cidade de Bauru/SP. A amostra foi composta por adultos com idade acima de 50 anos e através de entrevista foram coletadas informações sobre compra de medicamentos, prática de atividades físicas, condição econômica e tabagismo. Índice de massa corporal e perímetro abdominal compuseram marcadores de obesidade geral e abdominal. Como principais resultados encontrou-se que a compra de medicamentos foi maior entre mulheres, pessoas com mais de 65 anos, não-fumantes e naqueles com obesidade abdominal. De forma inversa, indivíduos ativos apresentaram menor compra de medicamentos quando comparados aos sedentários. Por fim, quando inatividade física e a obesidade abdominal foram agregadas em uma única variável, pessoas apenas inativas fisicamente e inativas fisicamente com obesidade abdominal apresentaram chances aumentadas de comprar medicamentos no último mês.
PHYSICAL ACTIVITY, ABDOMINAL OBESITY AND MEDICATION CONSUMPTION AMONG ADULTS: CROSS-SECTIONAL RETROSPECTIVE STUDY WITH USERS OF BRAZILIAN PUBLIC HEALTHCARE SYSTEM
Keywords: Motor activity; Obesity; Drug utilization; Atividade motora; Obesidade; Uso de medicamentos